(untitled) (Khairulummah, 2023)
The story of Bilqis is famous in Arabic poetry under the title "Maqam al-Hazn". This story is a famous historical event in the light of Qur’anic interpretation, which is based on the justice and fairness of Solomon (peace be upon him). Bilqis was a powerful queen of Yemen. One day, while traveling towards Sulaiman (peace be upon him), he was carrying wood in a green hook. Solomon (peace be upon him) said to the people with him, "Who will take these pieces of wood and bring them to the heavenly throne?" A single and alert person ran towards Bilqis and said that I have the best ability to compare your talismanic throne. Solomon (peace be upon him) displayed part of his kingdom, which was a sea floor, and demonstrated to Bilqis that he walked on the floor without being submerged in water. Bilqis was intrigued and ready to believe that Sulaiman (peace be upon him) had the ability to gather quotient. Later, Bilqis made a trip to Solomon where he demonstrated his strength and power. He made a throne and said, "Is there anyone who can bring this throne to me?" A jinn who was treated in a rebellious manner every time someone took the throne, which undoubtedly showed the power of Sulaiman (peace be upon him). Bilqis then made a small suggestion that a letter should be written to Sulaiman (peace be upon him) that would melt even a stone. They made one thing another and said that when this letter reached the presence of Solomon, he would recognize it. Solomon (peace be upon him) found the stone letter and he recognized it using strength and power. Balqis brought them undisputed control over their kingdom and they converted themselves to Islam. Bilqis’ story is full of justice, justice, strength, and concern. It shows that it is necessary to be powerful in order to recognize truth and reality and we must use our power with justice and fairness.